Pengaruh Teknologi Informasi Dan Lingkungan Kerja terhadap Kinerja Pegawai melalui kepuasan Kerja Pada Dinas Perdagangan Kota Padang - Yogi Tri Emerto; Marta Widian Sari; Vivi Nila Sari (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this research is to find out how much influence Information Technology and the Work Environment have on Employee Performance through Job Satisfaction in Padang City Trade Office Employees. The sample used was a saturated sample, because the entire population was sampled, namely 94 respondents. The data collection technique is through a questionnaire whose validity and reliability have been tested. Partial Least Square (PLS) was used to test the hypothesis in this research using SmartPLS 4.0. The results of this research show that there is a negative and insignificant influence of Information Technology on Job Satisfaction, a positive and significant influence of the Work Environment on Job Satisfaction, a negative and insignificant influence of Information Technology on Employee Performance, a negative and insignificant influence of the Work Environment on Employee Performance, a positive influence and significant Job Satisfaction on Employee Performance, negative and insignificant influence of Information Technology on Employee Performance through Job Satisfaction, positive and significant influence of the Work Environment on Employee Performance through Job Satisfaction.